Serum Levels of Alanine Aminopeptidase and Aggrecan in Women with Breast Cancer: A Comparative Study - Saja A. Hussein1 , Salam S. Ahmed2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The term “breast cancer” refers to a malignant tumor that has developed from cells in the breast and is a major public health problem in women throughout the world. It is the most common cancer among women both in developed and developing countries.(1) The aminopeptidases (AP) constitute a group of enzymes with closely related activities.(2) Aminopeptidases catalyze the cleavage of amino acids from the amino terminus of protein or peptide substrates. The enzyme exhibited low molecular weight of 58,000 by gel chromatograph.(3) Aggrecan is a proteoglycan, or a protein modified with large carbohydrates hormone; the human form of the protein is composed from 2316 amino acids long and can be expressed in multiple isoforms due to alternative splicing.(4) Materials and Method: This study was designed as a cross-sectional, hospital based study. Forty-two women with breast cancer were included in this study, their ages were from 24 to 70 years, and they were from the center and the periphery of Salah Al-din Governorate. Forty-four apparently healthy women with negative family history of breast cancer were included in this study as a control group, they ages were of a comparable age. By using a sterile disposable syringe, 10 mls of venous blood sample was drawn in a plain tube from each women included in this study for the serum measurement ofalanine aminopeptidase and Aggrecan by using ELIZA technique. Results: The mean serum level of alanine aminopeptidase was elevated in breast cancer women comparing with the control group (71.73±1.5 versus 15.29±0.9 ng/ml). The result was highly significant at a P value of less than 0.01. While the mean serum level ofaggrecan was found among women with breast cancer (41.81±11.5 ng/ml) compared to control group which was 7.27±3.6 ng/ml. The result was highly significant at a P value of less than 0.001. This study also found that there was a moderate positive correlation between AAP activity and S. aggrecan in breast cancer women (R<0.7). Conclusion: There were an increase in serum levels of both the alanine aminopeptidase and aggrecan in women with breast cancer.